Are Temporal Concepts Embodied? A Challenge for Cognitive Neuroscience - Kranjec, Alexander; Chatterjee, Anjan (Frontiers in Psychology, 2010)
Is time an embodied concept? People often talk and think about temporal concepts in terms of space. This observation, along with linguistic and experimental behavioral data documenting a close conceptual relation between space and time, is often interpreted as evidence that temporal concepts are embodied. However, there is little neural data supporting the idea that our temporal concepts are grounded in sensorimotor representations. This lack of evidence may be because it is still unclear how an embodied concept of time should be expressed in the brain. The present paper sets out to characterize the kinds of evidence that would support or challenge embodied accounts of time. Of main interest are theoretical issues concerning (1) whether space, as a mediating concept for time, is itself best understood as embodied and (2) whether embodied theories should attempt to bypass space by investigating temporal conceptual grounding in neural systems that instantiate time perception.